2016
DOI: 10.1159/000441667
|View full text |Cite
|
Sign up to set email alerts
|

Key Issues Associated with <b><i>Helicobacter pylori</i></b> Eradication

Abstract: Eradication of Helicobacter pylori causes improvement of gastric atrophy and intestinal metaplasia. Gastric acid secretion levels in corpus predominant gastritis increase after eradication. These changes can increase the risk of reflux esophagitis and low-dosage aspirin ulcers. Although eradication may reduce the overall risk of gastric cancer, a certain degree of risk remains, related to the extent of atrophy and intestinal metaplasia. Many post-eradication gastric cancers are the early depressed type, with l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 24 publications
0
12
1
Order By: Relevance
“…Helicobacter pylori eradication therapy is effective in the treatment and prevention of gastrointestinal diseases [1-8]. In Japan, triple therapy involving a proton pump inhibitor (PPI), amoxicillin (AMX), and clarithromycin (CAM) or metronidazole (MTZ) is recommended [9-12].…”
Section: Introductionmentioning
confidence: 99%
“…Helicobacter pylori eradication therapy is effective in the treatment and prevention of gastrointestinal diseases [1-8]. In Japan, triple therapy involving a proton pump inhibitor (PPI), amoxicillin (AMX), and clarithromycin (CAM) or metronidazole (MTZ) is recommended [9-12].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, overlooking GCAE on endoscopy may be the main cause of the increased prevalence of invasive gastric cancer after H. pylori eradication. For patients with a high gastric cancer risk who have undergone eradication therapy, careful attention must be paid to identify cancer lesions [23,24].…”
Section: Discussionmentioning
confidence: 99%
“…Thus, H. pylori eradication may prevent GC [6-11]. Although the risk factors of GC following H. pylori eradication have been reported in many studies [7, 11-20], few studies have examined the clinicopathological features of the disease [12, 14-17].…”
Section: Discussionmentioning
confidence: 99%
“…Although several studies showed no significant reduction in GC following H. pylori eradication [3-5], many studies have reported a significant reduction in GC development following H. pylori eradication [6-11]. These studies show that H. pylori eradication decreases the subsequent incidence of GC from 30 to 25%.…”
Section: Introductionmentioning
confidence: 99%